ANALISIS PERSEPSI SUAMI TENTANG KONTRASEPSI METODE OPERATIF PRIA (MOP) - Dyah Retnoningrum; Megawati; Irma (JURNAL SMART ANKes, 2023)
Based on contraceptive data use in Indonesia at the provincial, district and village levels, vasectomy contraceptive acceptor participants only occupy 0.0% compared to other KB. This study aims to determine how husbands perceive vasectomy contraception. This study was conducted in the Puding Besar Health Center work area. The researcher used a qualitative research method with a purposive sampling technique. The data collection technique used was an in-depth interview technique. The research sample consisted of 4 main informants, namely 2 male who were not vasectomy contraceptive acceptors and 2 vasectomy contraceptive acceptors. While the triangulation informants were 1 officer holding a contraceptive service program at the BKKBN Kab, Bangka and 1 officer holding a contraceptive service program at the Puding Besar Health Center. The results of this study showed that the perception of male about vasectomy contraception was influenced by several factors, namely supporting factors including knowledge, education, work, wife's medical history; enabling factors including access to information; driving factors including support from wife/family/community leaders. These factors give husbands the perception that vasectomy contraception can cause decreased productivity and work stamina as well as sexual relations, the husband's understanding is not egalitarian so that there is no equality of roles between husband and wife where the wife's job is to use contraception and take care of the household, while the husband's job is to work, besides that they assume that a man who uses contraception is a disgrace. The suggestion recommended by the researcher is that further research can be conducted related to the development of educational media to change the perception and behavior of husbands towards vasectomy contraception. Keywords: Couples Age Fertile, vasectomy, and Perception